Comparative response of a day-neutral and photoperiod-sensitive sorghum to delayed sowing or transplanting - Tenkouano, A.; Chantereau, J.; Sereme, P.; Touré, A. (African Journals Online, 1997)
Soil moisture deficit frequently occurs at the onset of the growing season and may cause crop failure. Resowing with early maturing varieties has often been the only alternative, besides transplanting. To assess the relative efficiency of the two resuce methods two sorghum (Sorghum bicolor (L.) Moench) cultivars, ‘IRAT204' (day-neutral) and ‘Nazongala' (photoperiod-sensitive), were grown in seven drought-prone environments in Western Africa. Grain yield of both cultivars was reduced by delayed sowing for both cultivars. Yield reduction was lowest when transplanting or resowing was done not later than two weeks from normal sowing time. Compensation levels were higher with the cultivar ‘IRAT204' than with ‘Nazongala'. While transplanting could contribute to partial yield loss recovery under erratic rainfall environments, it should not be considered as an option beyond four weeks from the normal sowing dates with day-neutral cultivars, due to their lack of phonological plasticity.